Design, synthesis and biological evaluation of novel hamamelitannin analogues as potentiators for vancomycin in the treatment of biofilm related Staphylococcus aureus infections. Issue 19 (1st October 2016) - Vermote, Arno; Brackman, Gilles; Risseeuw, Martijn D.P.; Coenye, Tom; Van Calenbergh, Serge
Graphical abstract: Abstract: Staphylococcus aureus is a frequent cause of biofilm-related infections. Bacterial cells within a biofilm are protected from attack by the immune system and conventional antibiotics often fail to penetrate the biofilm matrix. The discovery of hamamelitannin as a potentiator for antibiotics, recently led to the design of a more drug-like lead. In the present study, we want to gain further insight into the structure–activity relationship (S.A.R.) of the 5-position of the molecule, by preparing a library of 21 hamamelitannin analogues.